Sleep, Depression, and Fatigue in Late Postpartum. Issue 2 (March 2016) - Thomas, Karen A.; Spieker, Susan
Abstract: Purpose: To study the relation of infant characteristics and home environment on maternal sleep, depression, and fatigue in late postpartum. Study Design and Methods: Forty-two healthy mother–infant dyads completed a home-based study at infant age 32 weeks. Maternal measures included Patient Reported Outcomes Measurement Information System (PROMIS) sleep and wake disturbance, depression, and fatigue scales. Home regularity was assessed using the Confusion, Hubbub, and Order Scale (CHAOS). Infant sleep and regulation were measured respectively by the Brief Infant Sleep Questionnaire (BISQ) and Infant-Toddler Symptom Checklist (ITSC). Results: Significant correlations among maternal sleep and wake disturbance, fatigue, and depression were detected ( r = .519 to .746, p < .01), but not with infant variables. Home regularity was significantly related with maternal variables ( r = .597 to .653, p < .01). Clinical Implications: Regularity of the home environment appears to contribute to maternal sleep, depression, and fatigue. Implications for intervention include establishment of daily routines and household management to improve regularity and consequently improve maternal outcomes. Abstract : Sleep problems and fatigue are common issues among mothers of new babies. This study explores the relation between sleep, fatigue and depression for new mothers during the late postpartum period. Suggestions for helpful interventions are offered.